Suicidality treatment occurring in paediatrics (STOP) medication suicidality side effects scale in young people in two cohorts across Europe - Santosh, Paramala; Sala, Regina; Lievesley, Kate; Singh, Jatinder; Arango, Celso; Buitelaar, Jan K.; Castro-Fornieles, Josefina; Coghill, David; Dittmann, Ralf; Flamarique, Itziar; Hoekstra, Pieter J.; Llorente, Cloe; et al. (BMJ open, 2023)
Objectives As part of the ‘Suicidality: Treatment Occurring in Paediatrics (STOP)’ study, we developed and performed psychometric validation of an electronic-clinical-outcome-assessment (eCOA), which included a patient-reported-outcome (ePRO), an observer-rated-outcome (eObsRO) for parents/carers and a clinician-reported-outcome (eClinRO) that allows identification and monitoring of medication-related suicidality (MRS) in adolescents. - Design STOP: Prospective study: A two phase validation study to assess the impact of medication on suicidal ideations. - Setting Six participating countries: Netherlands, UK, Germany, France, Spain and Italy that were part of the Community’s Seventh Framework Programme (FP7/2007-2013) under grant agreement no. 261411. - Participants Cohort 1 consisted of 41 adolescent-completions, 50 parent-completions and 56 clinician-completions. Cohort 2 consisted of 244 adolescent-completions, 198 parent-completions and 240 clinician-completions from across the six countries. The scale was administered only to participants who have screened positive for the STOP-Suicidality Assessment Scale (STOP-SAS). - Results A total of 24 items for the development of the STOP-Medication Suicidality Side Effects Scale (STOP-MS3) were identified and three versions (for patients, parents and clinicians) of the STOP-MS3 were developed and validated in two separate study cohorts comprising of adolescents, their parents and clinicians. Cronbach’s α coefficients were above 0.85 for all domains. The inter-rater reliability of the STOP-MS3 was good and significant for the adolescent (ePRO), clinician (eClinRO) (r=0.613), parent (eObsRO) versions of the scale (r=0.394) and parent and clinician (r=0.347). Exploratory factor analysis identified a 3-factor model across 24 items for the adolescent and parent version of the scale: (1) Emotional Dysregulation, (2) Somatic Dysregulation and (3) Behavioural Dysregulation. For the clinician version, a 4-factor model defined the scale structure: (1) Somatic Dysregulation, (2) Emotional Dysregulation, (3) Behavioural Dysregulation and (4) Mood Dysregulation. - Conclusion These findings suggest that the STOP-MS3 scale, a web-based eCOA, allows identification and monitoring of MRS in the adolescent population and shows good reliability and validity.